Job Stress at Workplace and Recession: A Study of Stress in Employees of Selected Banks in Mumbai - Menon, Shreekumar (Prabandhan: Indian Journal of Management, 2010)
Stress means any form of tension or strain in the mind or body for which there is no release or outlet. It is not a condition that we made in the 20th century. The fact is stress has been around for since the beginning of the civilization. Stress by itself cannot hurt a person -it is how one responds to stress that counts, management of stress is important activity for every individual .The study of stress level of bank employees is an attempt to find the correlation between stress and working conditions prevalent in the banking sector. The results too proved the positive correlation between stress level and working conditions, male employees in the banks were more satisfied with working conditions as compared to female employees. Job satisfaction was high even with no stress management measures, this shows that employees are motivated to perform by proper work environment.